EVALUATION OF THE AMERICAN WATERWEED (ELODEA CANADENSIS MICHX.) AS SUPPLEMENTAL FOOD FOR THE NOBLE CRAYFISH, ASTACUS ASTACUS - D’AGARO E.; RENAI B.; GHERARDI F. (Knowledge and Management of Aquatic Ecosystems, 2004)
We conducted a preliminary study to evaluate the capacity of summerling Astacus astacus to consume the American waterweed (Elodea canadensis Michx.).under artificial rearing conditions. Summerling A. astacus (initial b.w.: 0.32 ± 0.02 g) were cultured (50 crayfish/m2) in 600l tanks for 89 days. The experimental design was composed of three treatments as follows: control diet (D) (crude protein: 40.9% DM; ether extract: 7.4% DM), elodea (E) (crude protein: 25.8% DM; ether extract: 1.4% DM) and control diet + elodea (D + E) with three replicates per treatment. Temperature, dissolved oxygen, and other water parameters were measured weekly (T: 20.1°C; O2: 7.2 mg/l; pH: 7.5; N-NH4: 0.05 mg/l; N-NO2: 0.01 mg/l; N-NO3: 29.9 mg/l). The relative growth rate was significantly (P < 0.01) higher in treatment D + E (195%) and D (143%) than in E (65%). The reduced growth observed in crayfish fed elodea only can probably be due to the lower dietary lipid level of the plant respect to the standard crayfish requirements. At the end of the experiment, the survival rate of A. astacus was higher (P < 0.05) for the treatment D + E (87%) and D (81%), compared to E (56%). Our results suggest that E. canadensis can be used as a non-expensive supplemental food in order to increase growth and survival in summerling noble crayfish. They also showed that A. astacus has the potential to consume this macrophyte in nature.